A Review on Isatin and Its Biological Activities - Chaudhari Anwar; Ugale Vinod Kumar; Dule Priya; Patil Kunal; Pawara Jayashri; Garkar Rushikesh; Jagtap Vaibhavkumar (Asian Journal of Pharmaceutical Research and Development, 2024)
Isatin, also (1H-indole-2,3-dione) is a natural molecular having a unique indole circle configuration. Erdmann and Laurent separated the phenomenon for the very first moment in 1841. Due to their numerous biological effects, this substance and its offspring have piqued researchers' interest. Isatin is widely recognized for its antibacterial, antiviral, anticonvulsant, anti-inflammatory, as and anti-cancer properties. The ability of this compound to react with an abundance of biological targets, including enzymes and receptors, makes it a useful scaffold for pharmacological design and development. Moreover, the isatin counterparts are under scrutiny regarding the potential use in creating of a heterocyclic a molecule, which are valuable in medicinal chemistry. The current study continues searching for new potential uses in forms of action for the isatin, highlighting its importance in the discipline of medicine and pharmaceutical synthesis.